2008
DOI: 10.1021/jf071998l
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Anthocyanins in the Liver, Eye, and Brain of Blueberry-Fed Pigs

Abstract: Dietary intervention with anthocyanins may confer benefits in brain function, including vision. Research to date indicates that animals have only a limited capacity to absorb anthocyanins, compared to other types of flavonoids. Pigs, which are a suitable model for human digestive absorption, were used to examine the deposition of anthocyanins in tissues including the liver, eye, and brain tissue. Pigs were fed diets supplemented with 0, 1, 2, or 4% w/w blueberries ( Vaccinium corymbosum L. 'Jersey') for 4 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
209
1
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(234 citation statements)
references
References 32 publications
8
209
1
6
Order By: Relevance
“…Thus, such an analysis would be valuable in future work to better understand how age differences impact on the potential effects of flavonoids on brain health. Although, the mechanisms by which flavonoids act in the brain are not clear, there is evidence to suggest that blueberry flavonoids can cross the blood-brain barrier (BBB) and reach the central nervous system, where they have the potential to directly regulate gene and protein expression in neurons [23,24,82]. However, at present it is unclear as to whether flavonoid-induced memory improvements are mediated exclusively centrally or whether other mechanisms such as stimulations in endothelial function and peripheral blood flow [83] also contribute.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, such an analysis would be valuable in future work to better understand how age differences impact on the potential effects of flavonoids on brain health. Although, the mechanisms by which flavonoids act in the brain are not clear, there is evidence to suggest that blueberry flavonoids can cross the blood-brain barrier (BBB) and reach the central nervous system, where they have the potential to directly regulate gene and protein expression in neurons [23,24,82]. However, at present it is unclear as to whether flavonoid-induced memory improvements are mediated exclusively centrally or whether other mechanisms such as stimulations in endothelial function and peripheral blood flow [83] also contribute.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that absorbed flavonoids and their metabolites are able to transverse the blood-brain-barrier [24][25][26] and may exert neuropharmacological actions at the molecular level, influencing signalling pathways, gene expression and protein function [27][28][29][30]. For instance, the beneficial effects of green tea, blueberry and Gingko Biloba on spatial memory have been shown to involve increases in hippocampal brain-derived neurotrophic factor (BDNF) [23,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Reports on the recovery of anthocyanins in the urine after consumption are up to 4% [34]. However, absorption of anthocyanins is greater than that which is recovered in the urine, because they are likely deposited into tissues [35].…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenol feeding studies on pigs have found polyphenols at micromolar concentrations in a variety of tissues and organs (Bieger et al, 2008;Kalt et al, 2008;Kalt et al, 2007), but one concern with these studies is that entrained blood may not have been completely removed, thus casting doubt on the actual concentrations in the tissues. On balance, it seems probable that polyphenols can access tissues and therefore cells in vivo, but probably in the form of conjugated metabolites or breakdown products, rather than the unconjugated forms tested in vitro.…”
Section: Bioavailability and Access Of Polyphenols To Mitochondria Inmentioning
confidence: 99%